Peliatan Style in Legong Keraton Lasem Performance - Ni Made Ruastiti; Ni Putu Ayu Aneska Rastini; Ni Luh Sustiawati (Randwick International of Social Science Journal, 2023)
The Legong Keraton Lasem dance is one of the classical Balinese dances featuring Panji's story about the love story of King Lasem and Diah Rangke Sari. This classical dance first appeared and developed in the palace environment of Bali. There have been many research results on the Legong Keraton Dance. However, there has not been any research that reveals the Legong Keraton Lasem and Peliatan Style. The problems are: 1) How did the Peliatan Style in Legong Lasem Performance Originate?; 2) What is the form of the Peliatan Style in Legong Keraton Lasem dance?. The purpose of this research was to reveal the existence of the Peliatan Style in Legong Keraton Lasem Performance, which has catapulted Bali's name into the eyes of the world. This research was conducted using qualitative methods. The source of the data for this study was the Legong performance, the dancers, musicians, artists, cultural observers, and related communities who were selected based on purposive sampling and snowball techniques. All data that has been collected through observation, interviews, and literature studies will be analysed using aesthetic theory, hierarchical theory, and practical theory. The results showed that the Peliatan Style in Legong Keraton has a distinctive characteristic in the volume of dance movements performed, which tends to be large with the maximum tilt of the dancer's body. It is different from how to dance the Legong Keraton in general. The Legong Keraton Lasem with Peliatan Style emerged due to two factors, namely internal and external factors. Internal factors include the talent possessed by the Legong dancers themselves. They dance with the aim of satisfying their material and spiritual needs. Meanwhile, encouragement from outside came from the environment of Peliatan Village, which is indeed famous for its artistic activities; its people are very passionate about art every day.